The features of operational component of social activity of student youth - Bazilenko, Anastasiya K. (Social Welfare: Interdisciplinary Approach, 2014)
In this article the operational component of students’ social activity research methodology has been grounded. The features of operational component of social activity of student youth have been analyzed, and levels of operational component have been characterized. As a result the levels of operational component of students’ social activity have been found out and described. The factors of operational component of social activity have been analyzed.
Keywords: social activity; operational component; student youth